The N-terminal dimerization is required for TDP-43 splicing activity - Lei-Lei Jiang (Nature Portfolio, 2017)
Abstract TDP-43 is a nuclear factor that functions in promoting pre-mRNA splicing. Deletion of the N-terminal domain (NTD) and nuclear localization signal (NLS) (i.e., TDP-35) results in mislocalization to cytoplasm and formation of inclusions. However, how the NTD functions in TDP-43 activity and proteinopathy remains largely unknown. Here, we studied the structure and function of the NTD in inclusion formation and pre-mRNA splicing of TDP-43 by using biochemical and biophysical approaches. We found that TDP-43 NTD forms a homodimer in solution in a concentration-dependent manner, and formation of intermolecular disulfide results in further tetramerization. Based on the NMR structure of TDP-43 NTD, the dimerization interface centered on Leu71 and Val72 around the β7-strand was defined by mutagenesis and size-exclusion chromatography. Cell experiments revealed that the N-terminal dimerization plays roles in protecting TDP-43 against formation of cytoplasmic inclusions and enhancing pre-mRNA splicing activity of TDP-43 in nucleus. This study may provide mechanistic insights into the physiological function of TDP-43 and its related proteinopathies.